Saluran Pemasaran Syariah Petani Cabai Desa Mejoyolosari Kabupaten Jombang - Fadhilah, Nurul; Ni'mah, Jamilatun; Sujianto, Agus Eko; Mashudi, Mashudi (STAI Auliaurrasyidin Tembilahan, 2023)
The purpose of this study was to analyze the marketing channels used by chili farmers in Mejoyolosari Village in marketing their chili yields. As well as to find out the marketing channels of chili farmers in Mejoyolosari Village from an Islamic economic perspective. This study used a qualitative method using case studies on chili farmers in Mejoyolosari Village, Gudo District, Jombang Regency. This study uses primary data and secondary data. This study uses the qualitative data analysis technique modeled by Miles and Huberman. The results of this study, namely chili farmers in Mejoyolosari Village, Gudo District, Jombang Regency use two types of marketing channels, namely vertical and horizontal marketing channels. For farmers with large land areas, it will be easier to use vertical marketing channels, while farmers with narrow lands will find it easier to use horizontal marketing channels to distribute chili yields. In general, chili farmers in Mejoyolosari Village in marketing chilies have applied sharia-compliant principles, being honest, maintaining trust (amanah), maintaining good relations (tabligh), a special group of chili farmers (fathonah).